Integrating irrigation realities into climate solutions: Evidence from Takeo, Cambodia - Jayasiri, M. M. J. G. C. N.; Flor, Rica Joy; Keo, Sokheng; Chuong, Thort; Then, Rathmuny; Urfels, Anton (International Rice Research Institute, 2025)
The climate crisis is fundamentally a water crisis. It is marked by rising temperatures, floods, droughts, unpredictable rainfall, declining water quality, and worsening water scarcity. These disruptions deeply affect agriculture by altering both the quantity and timing of irrigation water. For countries like Cambodia, where agriculture underpins food security and livelihoods, these shifts pose a serious threat. They also undermine progress toward the Sustainable Development Goals (SDGs), especially SDG 6 on Clean Water and SDG 2 on Zero Hunger. According to the Climate Risk Index 2024, Cambodia ranked among the top 20 countries most affected by climate-related disasters from 1993 to 2022 (Adil et al., 2025). Projections indicate that climate risks will intensify in the coming decades (WBG, 2024).